Forearm-Based Turnover Muscle Flaps for Elbow Soft-Tissue Reconstruction: A Comparison of Regional Coverage Based on Distal Flap Perfusion. Issue 1 (July 2018) - Avashia, Yash J.; Shammas, Ronnie L.; Poveromo, Luke P.; Dekker, Travis J.; Brubacher, Jacob W.; Richard, Marc J.; Ruch, David S.; Mithani, Suhail K.
Abstract : Background: Elbow wounds pose a reconstructive challenge. Prior studies have described the vascular anatomy of both the brachioradialis and flexor carpi ulnaris muscle flaps. The goal of this study was to describe the distal flap perfusion of the flexor carpi radialis, with a direct comparison of the brachioradialis, flexor carpi ulnaris, and flexor carpi radialis muscle flaps for coverage around the elbow. Methods: Six fresh-frozen upper extremity specimens were dissected for brachioradialis, flexor carpi radialis, and flexor carpi ulnaris flaps. Vascular data from prior studies were combined with our anatomical measurements to determine the area of perfused coverage around the elbow for the brachioradialis and flexor carpi ulnaris. The flexor carpi radialis flap distal vascular perfusion was examined separately with transverse sections at 1-cm intervals after India ink injections to determine distal flap perfusion and elbow coverage. Perfusion data were plotted on x and y axes over the posterior elbow. Results: The brachioradialis muscle covered an average of 56 percent of the x axis and 7.4 percent of the y axis. The flexor carpi ulnaris muscle covered an average of 90 percent of the elbow along the x axis and 23.3 percent of elbow along the y axis. The flexor carpi radialis covered an average of 34 percent of the x axis and 4.8 percent of the y axis. Conclusion: The flexor carpi ulnaris muscle provides the most versatile and robust coverage over the posterior elbow, followed by the brachioradialis muscle, which consistently provides coverage over the lateral epicondyle. Abstract : Supplemental Digital Content is available in the text.